Influence of Organic Esters on Portland Cement Hydration and Hardening - Duan-le Li; Da-peng Zheng; Dong-min Wang; Ji-hui Zhao; Cheng Du; Cai-fu Ren (Advances in Materials Science and Engineering)
This paper investigated the effect of organic compounds with ester groups on the hydration and hardening of cement. The effects of five kinds of organic compounds with ester groups (ethyl acetate, dimethyl oxalate, glyceryl triacetate, trimethyl phosphate, and triethanolamine borate) on hydration heat, hydration degree, setting time, mechanical properties, microstructure, and pore structure of hardened cement slurry were studied. The test results showed that esters can make the end time of cement hydration induction longer and delay the occurrence of the second exothermic peak. Also, the effect of five kinds of esters on the hydration and hardening of cement was basically followed by TG> TB> DMO> EAC> TMP. In terms of molecular structure, for organic compounds containing only ester groups, the higher the number of ester groups, the greater the effect on the hydration of cement. The introduction of other functional groups (such as phosphate or borate) will influence the effect of the esters.